2022
DOI: 10.1177/2473974x221088282
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Faculty Positions Among Top‐Ranked US Otolaryngology Departments

Abstract: Objective This study aims to characterize the top-ranked departments in otolaryngology to provide an indicator of the state of diversity within otolaryngology and to draw a comparison with other medical and surgical fields. Study Design This cross-sectional study examined the 20 highest-ranked otolaryngology programs according to the US News & World Report ranking of best hospitals for ear, nose and throat. Setting Academic otolaryngology departments in the United States. Methods Faculty demographic and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Specific to otolaryngology, a Canadian study revealed that female OTO‐HNS reported verbal and nonverbal sexual harassment more frequently compared with their male colleagues 21 . Pereira reported that females were underrepresented across all academic ranks in top‐rated U.S. otolaryngology programs, which unquestionably exacerbates these conditions 6 . These studies should motivate our medical community to invest in diversity initiatives and support the growing number of female physicians and surgeons worldwide.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Specific to otolaryngology, a Canadian study revealed that female OTO‐HNS reported verbal and nonverbal sexual harassment more frequently compared with their male colleagues 21 . Pereira reported that females were underrepresented across all academic ranks in top‐rated U.S. otolaryngology programs, which unquestionably exacerbates these conditions 6 . These studies should motivate our medical community to invest in diversity initiatives and support the growing number of female physicians and surgeons worldwide.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 The Otolaryngology-Head and Neck Surgery is predominantly comprised of White and male members, with underrepresentation of females and non-White practitioners in academic positions. 6 Moreover, recent data from the United States reported that Otolaryngology ranks last in its efforts to increase the number of African diaspora and Latin individuals. 7 Microaggressions are defined as "the everyday verbal, nonverbal, and environmental slights, snubs, or insults, whether intentional or unintentional, which communicate hostile, derogatory, or negative messages to target persons based solely upon their marginalized group membership."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissonance prompts questions about how diverse, inclusive, and welcoming the specialty is. [20][21][22][23][24][25][26] Certainly, data from the United States consistently show that least 60% of Otolaryngology workforce is white. 22,27,28 Correspondingly, neither African-Americans nor Latinos have ever been more than 10% of the workforce despite both groups occupying a higher percentage of the US population.…”
mentioning
confidence: 99%
“…Applicant‐reported data from the 2018 to 2020 match years in otolaryngology suggest an average spending of about $2437 for away rotations per applicant over the course of an application cycle 5 . Addressing the cost burden of away rotations could improve the pathway for URiM applicants in otolaryngology, which has significant race‐ and sex‐based disparities in resident selection and faculty promotion 6‐9 …”
mentioning
confidence: 99%